Glomeruläre Proteinurie - Physiologie und Pathophysiologie des „Nierenfilters“ - Haller, H.; Menne, J.; Schiffer, Mario (Nephrologe, 2013)
The efficient and complete filtration of blood plasma is one of the most important functions of the kidneys. Proteinuria is the pathological occurrence of protein molecules in urine due either to increased filtration in the glomerulus or to increased secretion or inefficient resorption in the tubules. The latter represents the least common cause of increased protein excretion. In this article the four different components of the glomerular filter, glycocalyx, fenestrated endothelial cells, basement membrane and epithelial podocytes with foot processes and slit membrane, will be briefly characterized and examples of albuminuria and proteinuria will be discussed. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Albuminuria; Glomerular filtration barrier; Kexwords: Renal function; Kidney disease; Plasma proteins